The Quantum Touch on Post Operative Pain and Mobilization Acceleration of Sectio caesarea Patients - Alwindo Razak; Suharsono Suharsono; Ari Santjaka (Sarana Ilmu Indonesia (Salnesia), 2025)
Surgical procedures or operations were treatments that used invasive methods. After SC, patients were usually given analgesics to relieve pain; however, despite receiving analgesics, patients still complained of pain. After SC, patients were advised to mobilize, but many patients still experienced pain and were afraid to mobilize due to concerns that the surgical sutures might open. Quantum Touch was a nonpharmacological intervention within nursing care that played a significant role in reducing pain levels and accelerating the mobilization process among patients. This study aimed to determine the efficacy of Quantum Touch in reducing postoperative pain and accelerating mobilization in post-cesarean section patients at RSUD Dr. MM. Dunda Limboto. This research was a quantitative study using a true experimental design to analyze the effect of Quantum Touch on pain and mobilization. The average pain score in the intervention group was 4,40, while in the control group it was 6,40. The results of the Mann-Whitney test showed that there was a significant effect of Quantum Touch on pain scores in SC patients (p = <0,001). Similarly, for mobilization, the statistical findings demonstrated that Quantum Touch significantly influenced mobilization acceleration in Sectio caesarea patients (p = 0,001). Quantum Touch was effective in reducing pain and accelerating mobilization in post-SC patients.